Survey of the crayfish plague pathogen presence in the Netherlands reveals a new Aphanomyces astaci carrier - Tilmans, M; Mrugała, A; Svoboda, J; Engelsma, M Y; Petie, M; Soes, D M; Nutbeam-Tuffs, S; Oidtmann, B; Roessink, I; Petrusek, A (Journal of invertebrate pathology, 2014)
North American crayfish species as hosts for the crayfish plague pathogen Aphanomyces astaci contribute to the decline of native European crayfish populations. At least six American crayfish species have been reported in the Netherlands but the presence of this pathogenic oomycete with substantial conservational impact has not yet been confirmed in the country. We evaluated A. astaci prevalence in Dutch populations of six alien crustaceans using species-specific quantitative PCR. These included three confirmed crayfish carriers (Orconectes limosus, Pacifastacus leniusculus, Procambarus clarkii), two recently introduced but yet unstudied crayfish (Orconectes cf. virilis, Procambarus cf. acutus), and a catadromous crab Eriocheir sinensis. Moderate levels of infection were observed in some populations of O. limosus and P. leniusculus. Positive results were also obtained for E. sinensis and two Dutch populations of O. cf. virilis. English population of the latter species was also found infected, confirming this taxon as another A. astaci carrier in European waters. In contrast, Dutch P. clarkii seem only sporadically infected, and the pathogen was not yet detected in P. cf. acutus. Our study is the first confirmation of crayfish plague infections in the Netherlands and demonstrates substantial variation in A. astaci prevalence among potential hosts within a single region, a pattern possibly linked to their introduction history and coexistence.
Keywords: Astacoidea; Animals; Carrier State; prevalence; přenašečství; zvířata; Nizozemsko; Prevalence; Netherlands; severní raci; Aphanomyces